Analysis of the Effect of a New Type of Nano-drug Carrier Preparation on the Pathological Changes in Lung and Inducible Nitric-Oxide Synthase Expression in Severe Sepsis: New Type of Nano-drug Carrier Preparation on the Pathological Changes - Sha, Yu; Wang, Jue; Wang, Zhao; Zhang, Xuesong; Chen, Jing (Cellular and Molecular Biology, 2022)
To explore the effect of a new type of nano-drug carrier preparation on the pathological changes in severe sepsis lung and inducible nitric oxide synthase (iNOS) expression, a new type of nano-drug carrier preparation was prepared based on RNA interference technology in this experiment. The new type of nano-drug carrier preparation was applied to the control group consisting of 120 rats and the experimental group consisting of 90 rats. The nano-drug carrier preparation group was given a drug injection, and the other group was injected with 0.9% sodium chloride injection. The data of mean arterial pressure, lactic acid, nitric oxide (NO) concentration, and iNOS expression level were recorded during the experiment. The results showed that the survival time of rats in each group was less than 36 hours before 24 hours, the mean arterial pressure of severe sepsis rats continued to decrease, while the mean arterial pressure and survival rate of rats given nano-drug carrier preparation increased significantly in the later stage of the experiment. The concentration of NO and lactic acid in severe sepsis rats increased significantly within 36 hours, while the concentration of NO and lactic acid in rats of the nano group decreased in the later stage of the experiment. The expression level of iNOS mRNA in lung tissue of rats in the severe sepsis group increased significantly during 6-24 hours and began to decrease after 36 hours. The expression level of iNOS mRNA in rats injected with nano-drug carrier preparation decreased significantly. In summary, the new type of nano-drug carrier preparation can improve the survival rate and mean arterial pressure of severe sepsis rats, decrease the concentration of NO and lactic acid and the expression level of iNOS, selectively silence the inflammatory factors in lung cells, reduce the inflammatory reaction, inhibit the synthesis of NO, and correct the oxygenation reaction in the body, which was of great significance for the clinical treatment of severe sepsis lung pathological changes.